Hubungan Faktor Pemilihan Makanan Jajanan Siswa Di Sekolah Dasar Inpres Maccini Sombala Kota Makassar - Hatta, Herman; J. Hadi, Anto; Yetti R, Erni; Tombeg, Zadrak; Manggabarani, Saskiyanto (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2018)
ABSTRACT Included schooled child agglomerate vulnerable nutrient. Consumption wont food on schooled child, particularly on schooled rest hour interval. But consumption wont food healthy still haven't a lot of proprietary by school child. This research is executed at Inpres Maccini Sombala Elementary School Makassar. Observational type that is utilized is observasional with approaching cross sectional study which is to analysis associated factor alimentary election on student at Inpres Maccini Sombala Elementary School Makassar 2017. This observational sample is Elementary School student with taking sample purphosive sampling with amount 146 samples. Acquired observational result that science concerning alimentary election on student with value p (0,000) < 0,05, pocket money concerning alimentary election on student with value p (0,003) < 0,05, alimentary type concerning alimentary election on student with value p (0,009) < 0,05 and eating frequency concerning alimentary election on student with value p (0,025) < 0,05. This observational conclusion is gnostic, pocket money, alimentary type, frequency eats to communicate wont food election on student. To side school shall make a abode to notice wont food existence school child and needs to get special interest.